Tinjauan Yuridis Normatif Perlindungan Anak dalam Perspektif Konsep Hadhanah dan Undang-Undang Nomor 35 Tahun 2014 - Niken Sylvia Puspitasari; Muhammad Giri Herlambang; Alwan Abidin; Riyanmar Fayat Zabihullah (Pusat Penelitian dan Pengabdian Masyarakat (P3M), Sekolah Tinggi Ilmu Islam dan Bahasa Arab (STIBA) Makassar, 2024)
This study aims to explain the concept of Islamic law through the concept of hadhanah in the effort to protect Indonesian children. In Law No. 35 of 2014, which has been ratified by the government, it is emphasized that the protection of Indonesian children from all forms of discrimination and violence is a priority. Since the majority of people in Indonesia are Muslim, Islamic values and standards certainly influence the upbringing and education of children. Child neglect is one form of maltreatment and violence experienced by children and constitutes a violation of children's human rights, whether intentional or unintentional. A normative juridical research method, which is based on library research, is used as the research methodology. Based on the research findings, Islamic law itself teaches how to protect children, and the government, society, and parents have a very important role in establishing policies that benefit children and uphold human rights. The results of this study indicate that Law No. 35 of 2014 has fulfilled the concept of hadhanah in Islamic jurisprudence and has involved all parties in protecting children. This law also explains child protection in the fields of religion, health, education, and social matters.